Video compression techniques: an overview - Abomhara, Mohamed; Khalifa, Othman Omran; Omar, Zakaria; Zaidan, Aos Alaa; Zaidan, Bilal Bahaa; Rame, A. (Asian Network for Scientific Information, 2010)
In this study, a new comparative study of video compression techniques was presented. Due to the rapid developments in internet technology and computers, popularity of video streaming applications is rapidly growing. Therefore today, storing and transmitting uncompressed raw video requires large storage space and network bandwidth. Special algorithms which take these characteristics of the video into account can compress the video with high compression ratios. This study demonstrates the representative efforts on video compression and presents the properties and limitations of: H.261, H.263, MPEG-1, MPEG-2, MPEG-4, MPEG-7 and H.264. However, we show that H.264 entails significant improvements in coding efficiency, latency, complexity and robustness. It provides new possibilities for creating better video encoders and decoders that provide higher quality video streams at maintained bit-rates (compared to previous standards), or, conversely, the same quality video at a lower bit-rate Hence, appropriate video compression techniques that meet video applications requirements have to be selected.